Serum iron levels in schizophrenic patients with or without akathisia - Kuloglu, M; Atmaca, M; Üstündag, B; Canatan, H; Gecici, O; Tezcan, E (Elsevier, 2003)
The pathophysiology of akathisia still remains controversial. Iron deficiency was proposed to be an important factor in the development of akathisia. In the present study, it was aimed to compare levels of serum iron and linked variables in chronic akathisic (n=30), and non-akathisic patients (n=30) with schizophrenia and healthy controls (n=30) because of the controversy in the association of iron and akathisia. The Barnes Akathisia Scale for akathisia and Simpson-Angus Rating Scale for extrapyramidal side effects were used. Serum iron and linked variables and hematological profile of the patients and control subjects were determined. Serum iron levels were significantly lower both in akathisic and non-akathisic groups compared to the control group (P<0.001). Moreover, akathisic patients had significantly lower iron levels than non-akathisic patients (P<0.05). Total iron binding capacity was significantly higher in patients with akathisia compared to the control group (P<0.01). Although non-akathisic patients had a mild increase in total iron binding capacity, it was not statistically significant compared to the control group (P>0.05). Ferritin levels were determined to be significantly lower in both groups compared to the control group (P<0.01). In addition, there was a significant difference in ferritin levels between the patients with and without akathisia (P<0.05). In conclusion, our results support the hypothesis that an association between akathisia and iron metabolism exists. (C) 2002 Elsevier Science B.V./ECNP All rights reserved.
Keywords: serum iron; akathisia; ferritin; total iron binding capacity